The effects of institutional quality and biocapacity on inclusive human development in Sub-Saharan Africa - Giyoh G. Nginyu; Dobdinga Cletus Fonchamnyo; Boniface Ngah Epo; Simplice Asongu (African Governance and Development Institute (AGDI), 2023)
The purpose of this study is to investigate the effect of biocapacity and institutional quality on inclusive human development in Sub-Saharan Africa. Using system-GMM on a sample of 39 countries, it is found that institutional quality increases inclusive human development and all its components. It is also established that biocapacity positively affects inclusive human development and the underlying positive effect is driven by the inclusive health component of inclusive human development and not by the inclusive education and inclusive income components of inclusive human development. A keen follow-up of environmental laws is a safe path for inclusive human development in Sub-Saharan Africa.
Keywords: G20; I10; I32; O40; P37; 330; biocapacity; institutional quality; inclusive human development